2009
DOI: 10.1038/nmat2591
|View full text |Cite|
|
Sign up to set email alerts
|

Biofunctionalized magnetic-vortex microdiscs for targeted cancer-cell destruction

Abstract: Nanomagnetic materials offer exciting avenues for probing cell mechanics and activating mechanosensitive ion channels, as well as for advancing cancer therapies. Most experimental works so far have used superparamagnetic materials. This report describes a first approach based on interfacing cells with lithographically defined microdiscs that possess a spin-vortex ground state. When an alternating magnetic field is applied the microdisc vortices shift, creating an oscillation, which transmits a mechanical force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
512
0
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(534 citation statements)
references
References 36 publications
9
512
0
13
Order By: Relevance
“…10 Vortices are one type of topological defects characterized by an in-plane magnetization with a clockwise (CW) or counter-clockwise (CCW) chirality and a central core with an out-of-plane magnetization (up or down polarity).…”
mentioning
confidence: 99%
“…10 Vortices are one type of topological defects characterized by an in-plane magnetization with a clockwise (CW) or counter-clockwise (CCW) chirality and a central core with an out-of-plane magnetization (up or down polarity).…”
mentioning
confidence: 99%
“…31 Nevertheless, their exceedingly small surface area limits their efficiency as drug carriers. An alternative approach is to use magnetic vortices, 34 also with virtually zero magnetic remanence, but disks of a few micrometers in diameter are needed to form such magnetic configurations. Hence, magnetic vortices can be rather impractical for most biological purposes.…”
Section: Or Inmentioning
confidence: 99%
“…In terms of overcoming these inconveniences, magnetofection provides an alternative way of targeted gene delivery using magnetic fields. As a result, many studies related to gene delivery via magnetofection are now available in the literature [1][2][3][4][5][6][7][8][9][10][11]. For example, Scherer et al…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the transfection efficiency was significantly enhanced due to simultaneous exposure of cells to ultrasound and magnetic field. Kim et al [9] reported on the interfacing of whole cells with biocompatible lithographically defined ferromagnetic microdiscs with a spin-vortex ground state. It was found that spin-vortexmediated stimulus caused compromised integrity of cellular membranes and initiation of programmed cell death.…”
Section: Introductionmentioning
confidence: 99%